Optimization of Subsurface Drain Spacing and Depth for Sugarcane under Waterlogged Vertisols of Canal/Lift Irrigated Areas of Maharashtra, India : Drain spacing and depth for sugarcane - Rathod, Shrimant (Journal of Soil Salinity and Water Quality, 2023)
The problems of waterlogging, salinity and sodicity declined the productivity of different crops especially sugarcane in recent decades of Maharashtra. Subsurface drainage is required to combat the twin problems of irrigation induced soil salinity and waterlogging. The field experiments for increasing sugarcane productivity in waterlogged Vertisols through subsurface drainage system were conducted at Agricultural Research Station, Kasbe Digraj, Sangli, Maharashtra (India) during 2012-13 to 2017-18. Four drain spacings (10, 20, 30 and 40 m) as main factor and three drain depths (0.75, 1.0 and 1.25 m) as sub-factor in split plot design were included for achieving objectives. The results revealed that 40 m drain spacing recorded significantly highest pooled mean height of sugarcane, milleable cane height, No. of internodes, No. of milleable canes per clump, cane yield followed by 30, 20 and 10 m. Whereas, the significantly highest pooled mean height of milleable cane, weight of single milleable cane, cane yield, CCS (%) and sugar yield were observed under 1.25 m drain depth followed by 1.0 and 0.75 m. The economic analysis revealed that 40 m drain spacing and 1.25 m depth recorded significantly highest pooled mean of B:C ratio, gross and net monetary returns. The interaction effect was non-significant. Thus, the drain spacing of 40 m and 1.25 m depth are recommended for optimum drainage, less NO3-N losses, economically optimal growth, yield and quality dynamics of sugarcane under waterlogged Vertisols of canal/lift irrigated areas of Maharashtra, India.